Exploring the efficiency of caprylic acid and quaternary ammonium salt-based deep eutectic solvents for separation of CO2 and H2S from gas mixtures using molecular dynamics simulations and COSMO-RS - Samaneh Barani Pour; Mitra Dabbagh Hosseini pour; Jaber Jahanbin Sardroodi; Alireza Rastkar Ebrahimzadeh; Gholamreza Pazuki; Mohammad Sadegh Avestan (Chemical Engineering Journal Advances)
In the present study, quaternary ammonium salts (QAS) and caprylic acid based deep eutectic solvents (DES) were employed for the separation of CO2 and H2S from natural gas (NG). To elucidate the extraction mechanisms of H2S from natural gas (NG), we employed molecular dynamics (MD) simulations to investigate the intermolecular interactions between the gases and the eutectic solvents. Our comprehensive analysis aimed at enhancing the understanding of quaternary ammonium salt (QAS) absorption capability in H2S extractions including combined distribution functions (CDFs), which encompass radial distribution functions (RDFs), angular distribution functions (ADFs), hydrogen-bonding networks, density profiles, spatial distribution functions (SDFs), and the non-bond energies between H2S and the DES components, all measured at 310 K. Additionally, we calculated the solubility of H2S and CO2 gases as well as the solubility selectivity and diffusivity selectivity parameters to evaluate the performance of the QAS-based DES in sweetening processes of NG. The results represent that eutectic solvents based on quaternary ammonium chloride are effective for H2S adsorption and show selectivity for H2S in gas mixtures. Furthermore, the COSMO-RS model was used to predict the solubility of various gases (H2S/CO2) in the QAS-based DES, providing further insights into their effectiveness.